Fibroblast gene expression following asthmatic bronchial epithelial cell conditioning correlates with epithelial donor lung function and exacerbation history. Issue 1 (December 2018) - Reeves, Stephen; Barrow, Kaitlyn; Kolstad, Tessa; White, Maria; Rich, Lucille; Wight, Thomas; Debley, Jason
Abstract Airway remodeling may contribute to decreased lung function in asthmatic children. Bronchial epithelial cells (BECs) may regulate fibroblast expression of extracellular matrix (ECM) constituents and fibroblast-to-myofibroblast transition (FMT). Our objective was to determine if human lung fibroblast (HLF) expression of collagen I (COL1A1), hyaluronan synthase 2 (HAS2), and the FMT marker alpha-smooth muscle actin (α-SMA) by HLFs conditioned by BECs from asthmatic and healthy children correlate with lung function measures and exacerbation history among BEC donors. BECs from asthmatic (n = 23) and healthy children (n = 15) were differentiated at an air-liquid interface (ALI) and then co-cultured with HLFs for 96 hours. Expression of COL1A1, HAS2, and α-SMA by HLFs was determined by quantitative polymerase chain reaction (qPCR). FMT was quantified by measuring HLF cytoskeletal α-SMA by flow cytometry. Pro-collagen Iα1, hyaluronan (HA), and PGE2 were measured in BEC-HLF supernatant. Correlations between lung function measures of BEC donors, and COL1A1, HAS2, and α-SMA gene expression, as well as supernatant concentrations of HA, pro-collagen Iα1, hyaluronan (HA), and PGE2 were assessed. We observed that expression of α-SMA and COL1A1 by HLFs co-cultured with asthmatic BECs was negatively correlated with BEC donor lung function. BEC-HLF supernatant concentrations of pro-collagen Iα1 were negatively correlated, and PGE2 concentrations positively correlated, with asthmatic BEC donor lung function. Expression of HAS2, but not α-SMA or COL1A1, was greater by HLFs co-cultured with asthmatic BECs from donors with a history of severe exacerbations than by HLFs co-cultured with BECs from donors who lacked a history of severe exacerbations. In conclusion, α-SMA and COL1A1 expression by HLFs co-cultured with BECs from asthmatic children were negatively correlated with lung function measures, supporting our hypothesis that epithelial regulation of HLFs and airway deposition of ECM constituents by HLFs contributes to lung function deficits among asthmatic children. Furthermore, epithelial regulation of airway HAS2 may influence the susceptibility of children with asthma to experience severe exacerbations. Finally, epithelial-derived PGE2 is a potential regulator of airway FMT and HLF production of collagen I that should be investigated further in future studies.